Plasmodium vivax resistance to chloroquine in Dawei, southern Myanmar. - Guthmann, J; Pittet, A; Lesage, A; Imwong, M; Lindegardh, N; Min Lwin, M; Zaw, T; Annerberg, A; de Radiguès, X; Nosten, F (2008)
OBJECTIVE: To assess the efficacy of chloroquine in the treatment of Plasmodium vivax malaria in in Dawei District, southern Myanmar. METHODS: Enrolled patients at Sonsinphya clinic >6 months of age were assessed clinically and parasitologically every week for 28 days. To differentiate new infections from recrudescence, we genotyped pre- and post-treatment parasitaemia. Blood chloroquine was measured to confirm resistant strains. RESULTS: Between December 2002 and April 2003, 2661 patients were screened, of whom 252 were included and 235 analysed. Thirty-four per cent (95% CI: 28.1-40.6) of patients had recurrent parasitaemia and were considered treatment failures. 59.4% of these recurrences were with a different parasite strain. Two (0.8%) patients with recurrences on day 14 had chloroquine concentrations above the threshold of 100 ng/ml and were considered infected with chloroquine resistant parasites. 21% of failures occurred during the first 3 weeks of follow-up: early recurrence and median levels of blood chloroquine comparable to those of controls suggested P. vivax resistance. CONCLUSIONS: Plasmodium vivax resistance to chloroquine seems to be emerging in Dawei, near the Thai-Burmese border. While chloroquine remains the first-line drug for P. vivax infections in this area of Myanmar, regular monitoring is needed to detect further development of parasite resistance.